Impact of Helicobacter pylori eradication on the anti-secretory efficacy of lansoprazole in gastroesophageal reflux disease patients - (:unkn) unknown (WILEY, 2005)
Background: Helicobacter pylori eradication was recommended for the prevention of atrophic gastritis in gastroesophageal reflux disease (GERD) patients on long-term omeprazole treatment. It has been also shown that the treatment with proton pump inhibitors produces lower intragastric pH after H. pylori eradication in subjects with peptic ulcer and healthy individuals. The aim of the present study was to test the hypothesis of whether the efficacy of lansoprazole is reduced after the eradication of H. pylori in GERD patients with peptic esophagitis. Methods: Eight-hour intragastric pH recordings were performed before and after an 8-day course of lansoprazole (30 mg once daily) in 10 H. pylori-positive male patients with reflux esophagitis and were repeated after the H. pylori eradication. Intragastric acidity was measured by using an antimony electrode placed 10 cm below the cardia. Results: Baseline median preprandial, post-prandial, total intragastric pH and the percentage of time with pH < 3 were not different before and after H. pylori eradication without lansoprazole treatment. During lansoprazole treatment, median post-prandial intragastric pH was lower (4 vs 2.7; P < 0.05) and the percentage of time with pH < 3 was longer (3.4%vs 41.8%; P < 0.05) after H. pylori eradication. Median total intragastric pH tended to be lower after eradication but no difference was found in preprandial median pH. Conclusions: In patients with reflux esophagitis treated with lansoprazole, intragastric pH increased significantly when H. pylori was present, especially in the post-prandial period, whereas baseline pH remained unchanged after H. pylori eradication. (C) 2005 Blackwell Publishing Asia Pty Ltd.
Keywords: gastritis; gastroesophageal reflux disease; Helicobacter pylori; lansoprazole; acid secretion; GASTRIC-ACID-SECRETION; INTRAGASTRIC PH; INFECTION; OMEPRAZOLE; ESOPHAGITIS; BREAKTHROUGH; AUGMENTS; INJURY; CURE